(3JGQjN UfYGA Gdjefs - (3GdUfYGfj , CMeO Hf YHO Gddg Hf eMeO GdQGRj GdUfYGfj Gdjefj, CHhGdYHGS,J (B460 (3g` s
(3BNQgG (B:s
(3hbGd gPg GdHFQ GdJi Cdbi ajgG GdbJjd ai NdGaI YeQ Hf GdNWGH hcJH Edi hGdjg jYdi Hf CejI jCeQg HbJd LejY ef TGQc ai bJdge Je GdcJGH s
(3fSNI KGfjIs
(3hgh cJGH ai JGQjN eOjfI UfYGA bGYOI Gdjefs
(3heG LGhQgG ef GdHdOGf hPcQ MhGOKgG hhbGFYgG hdhcgG hhdGOJgG ef LgI GdfHi Udi Gddg Ydjg hSde hGdNdaGA ef HYOg hZjQ Pdcs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs